Model and Optimal Solution of Single Link Pricing Scheme Multiservice Network - Irmeilyana Irmeilyana; Indrawati Indrawati; Fitri Maya Puspita; Juniwati Juniwati (Universitas Ahmad Dahlan, 2014)
This paper discussed the new improved and modified internet pricing scheme in multiservice networks [1]. This new improved scheme is created to set up the base price, quality premium and Quality of service (QoS). This scheme has the purposes to help Internet Service Provider (ISP) in maximizing the revenue and contribute better quality of service to the users. The objective function will be formed to set up the base price and quality premium as a vaiable or a constant. The models used are in nonlinear forms and solved by using LINGO 11.0 to get the optimal solution. The results show that for each cases of improved scheme, ISP gets better optimal solutions by varying or fixing the base price and quality premium.